First identification of the pathogen causing tumor malformations in evergreen oaks in Spain - Martín-Santafé, María; Sánchez-Durán, Sergio; Batlle-Durany, Assumpció; Laviña-Gomila, Amparo; Barriuso-Vargas, Juan (Forest Systems, 2014)
Aim of study: In recent years an increase in pests and diseases associated with truffle plantations has been detected in Spain. The appearance of tumor malformations in trunks and branches of Quercus ilex L. must be highlighted. These bumps have expanded dramatically since the increase in the number and density of truffle plantations. This pathology is not only found in plantations, but also in forests, and in trees of all ages. Area of study: the eastern mountains and the truffle plantations of the Iberian Peninsula. Material and methods: Positive results were obtained by using two types of PCR: Real-Time PCR and nested-PCR. They were carried out with primers that amplified 16S ribosomal gene sequences that are common to all known phytoplasmas. Main result: The disease manifests itself as an irregular thickening in branches of any age and in the trunk that results in the woody tissue cracking open, forming wounds. The affected branches usually undergo necrosis and in case of affecting the trunk, the tree will eventually die. After an extensive literature review and several failed attempts to isolate fungal and bacterial species from these tumors and wounds, the disease-causing organism has been identified as a Candidatus Phytoplasma. Research highlights: The appearance of this disease may endanger the profitability of an a priori profitable crop. Due to the intrinsic characteristics of the organism, and knowing that no phytosanitary treatment is able to control phytoplasmas, future works should be directed towards identifying the transmitter in order to control the disease. Key words: Candidatus Phytoplasma; PCR; Quercus ilex; black truffle; Tuber melanosporum.